2020
DOI: 10.1016/j.brs.2019.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar transcranial magnetic stimulation: The role of coil type from distinct manufacturers

Abstract: a b s t r a c tBackground: Stimulating the cerebellum with transcranial magnetic stimulation is often perceived as uncomfortable. No study has systematically tested which coil design can effectively trigger a cerebellar response with the least discomfort. Objective: To determine the relationship between perceived discomfort and effectiveness of cerebellar stimulation using different coils: MagStim (70 mm, 110 mm-coated, 110-uncoated), MagVenture and Deymed. Methods: Using the cerebellar-brain inhibition (CBI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…The MEPs amplitudes from both unconditioned and conditioned MEPs were considered for analysis. As in previous studies [ [31] , [32] , [33] , [34] ], we excluded extreme MEP amplitudes in which responses were more than 1.5 times above the third quartile or below the first quartile of the interquartile range. Trials were also excluded if ongoing muscle activity was detected (EMG signal >50 μV within 100 ms before TMS pulse) [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…The MEPs amplitudes from both unconditioned and conditioned MEPs were considered for analysis. As in previous studies [ [31] , [32] , [33] , [34] ], we excluded extreme MEP amplitudes in which responses were more than 1.5 times above the third quartile or below the first quartile of the interquartile range. Trials were also excluded if ongoing muscle activity was detected (EMG signal >50 μV within 100 ms before TMS pulse) [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…The coil was positioned in this manner to ensure optimal stimulation of the cerebellum without directly activating the spinal cord [9,40]. For all measures requiring cerebellar stimulation, we set the TMS intensity to 60% of maximum stimulator output (MSO), as this value does not active the brainstem and is easily tolerated by participants [16,21].…”
Section: Cerebellar-m1 Connectivity (Cbi)mentioning
confidence: 99%
“…This is most likely due to the substantial interindividual variability and lack of neural predictors in response to brain stimulation. In part, this is explained by the limited range in which stimulation can target the cerebellum [21], including where stimulation should be applied (e.g. location of figure-eight TMS coil) and which montage should be selected (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Across all studies, we found nine individuals who displayed a BaMT response under 75% MSO (mean cerebellar conditioning intensity, 68.57 6 0.75; Table 1). To assess cerebellar-M1 connectivity (CBI), the double-cone coil was then placed over the right cerebellar cortex 3 cm lateral to the inion, with the stimulator current directed downward (Hardwick et al, 2014;Ginatempo et al, 2019;Spampinato et al, 2020). Moreover, the TS over left M1 was delivered using a 70-mm-diameter figure-of-eight coil, and the intensity was set to a stimulator output that elicited ;1 mV MEP response.…”
Section: Participantsmentioning
confidence: 99%